2009
DOI: 10.1897/08-162.1
|View full text |Cite
|
Sign up to set email alerts
|

Brominated and chlorinated flame retardants in Lake Ontario, Canada, lake trout (Salvelinus namaycush) between 1979 and 2004 and possible influences of food-web changes

Abstract: Concentrations of non-polybrominated diphenyl ether (PBDE) brominated (hexabromocyclododecane [HBCD], 1,2-bis[2,4,6-tribromophenoxy]ethane [BTBPE], and pentabromoethylbenzene [PEB]) and chlorinated (Dechlorane Plus [DP] as well as short- and medium-chain chlorinated paraffins [SCCP and MCCP, respectively]) flame retardants were evaluated in archived Lake Ontario, Canada, lake trout (Salvelinus namaycush) samples collected between 1979 and 2004. Polybrominated diphenyl ethers also were analyzed to provide a poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
107
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 46 publications
10
107
3
Order By: Relevance
“…SE and PLE (including ASE) were applied to solid samples, while LLE and SPE (e.g., C18) were used for liquid sample extraction . Mixed organic solvents, such as n-hexane/ acetone (v/v: 1/1) (Hoh et al, 2006;Ismail et al, 2009;Peverly et al, 2015;Ren et al, 2008;Salamova et al, 2014;Zhang et al, 2011a, b), n-hexane/dichloromethane (v/v: 1/1) (De la Möller et al, 2010Möller et al, , 2011Zhang et al, 2013), and the same mixtures with different proportions (Kang et al, 2010;Tomy et al, 2008;Wu et al, 2010;Xian et al, 2011), were commonly used for extraction.…”
Section: Sample Extraction and Clean-upmentioning
confidence: 99%
See 2 more Smart Citations
“…SE and PLE (including ASE) were applied to solid samples, while LLE and SPE (e.g., C18) were used for liquid sample extraction . Mixed organic solvents, such as n-hexane/ acetone (v/v: 1/1) (Hoh et al, 2006;Ismail et al, 2009;Peverly et al, 2015;Ren et al, 2008;Salamova et al, 2014;Zhang et al, 2011a, b), n-hexane/dichloromethane (v/v: 1/1) (De la Möller et al, 2010Möller et al, , 2011Zhang et al, 2013), and the same mixtures with different proportions (Kang et al, 2010;Tomy et al, 2008;Wu et al, 2010;Xian et al, 2011), were commonly used for extraction.…”
Section: Sample Extraction and Clean-upmentioning
confidence: 99%
“…Cleanup or purification of the environmental sample extracts could be done by a silica gel column (Hoh et al, 2006;Ismail et al, 2009;Ren et al, 2008;Salamova et al, 2014) or a multilayer column packed with acidic and basic silica gel Kang et al, 2010;Liu et al, 2014;Wu et al, 2010;Zhang et al, 2013) except for sediment. It was also reported that alumina and Florisil columns, as well as commercial SPE column (i.e., Oasis® HLB) were effective (Cequier et al, 2015;Zhang et al, 2011b;Zheng et al, 2015a).…”
Section: Sample Extraction and Clean-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that some halogenated flame retardants are potentially toxic, bio-accumulative, ubiquitous and persistent in the environment (Ismail et al, 2009;Muir and Howard, 2006), especially polybrominated diphenyl ethers (PBDEs) (de Wit, 2002;Law et al, 2003Law et al, , 2006Law et al, , 2008Talsness, 2008). Penta-and octa-BDEs were regulated in Europe and the Unites States (Hites, 2004) and were added as new persistent organic pollutants (POPs) to the Stockholm Convention at the 4th Conference of the Parties (COP-4) held in May 2009 (www.pops.int).…”
Section: Introductionmentioning
confidence: 99%
“…It was only recently detected in the environment (Hoh et al, 2006) even though it has been produced for almost fifty years. Most published research on DP has focused on the Great Lakes area (Hoh et al, 2006;Qiu et al, 2007;Qiu and Hites, 2008;Sverko et al, 2008Sverko et al, , 2010Tomy et al, 2007), which results suggest that DP is bio-available and bio-accumulative (Gauthier and Letcher, 2009;Ismail et al, 2009). As for Asia, Qiu and Hites (2008) analyzed the tree barks from China and Korea and suggested that there might be Asia-specific sources of DP to the environment.…”
Section: Introductionmentioning
confidence: 99%